Impact of patient characteristics on efficacy and safety of once-weekly semaglutide versus dulaglutide: SUSTAIN 7 post hoc analyses. Issue 11 (16th November 2020) - Pratley, Richard E; Aroda, Vanita R; Catarig, Andrei-Mircea; Lingvay, Ildiko; Lüdemann, Jörg; Yildirim, Emre; Viljoen, Adie
Abstract : Objective: In SUSTAIN 7, once-weekly semaglutide demonstrated superior glycated haemoglobin (HbA1c ) and body weight (BW) reductions versus once-weekly dulaglutide in subjects with type 2 diabetes (T2D). This post hoc analysis investigated the impact of clinically relevant subject characteristics on treatment effects of semaglutide versus dulaglutide. Design: Analyses by baseline age (<65, ≥65 years), sex (male, female), diabetes duration (≤5, >5–10, >10 years), HbA1c (≤7.5, >7.5–8.5, >8.5% (≤58, >58–69, >69 mmol/mol)) and body mass index (BMI) (<30, 30–<35, ≥35 kg/m 2 ). Setting: 194 sites; 16 countries. Participants: Subjects with T2D (n=1199) exposed to treatment. Interventions: Semaglutide 0.5 mg versus dulaglutide 0.75 mg (low-dose comparison); semaglutide 1.0 mg versus dulaglutide 1.5 mg (high-dose comparison), all subcutaneously once weekly. Primary and secondary outcome measures: Change in HbA1c (primary endpoint) and BW (confirmatory secondary endpoint) from baseline to week 40; proportion of subjects achieving HbA1c targets (<7%, ≤6.5% (<53, ≤48 mmol/mol)) and weight-loss responses (≥5%, ≥10%) at week 40; and safety. Results: HbA1c and BW reductions (estimated treatment difference ranges: –0.22 to –0.70%-point; –1.76 to –3.84 kg) and proportion of subjects achieving HbA1c targets and weight-loss responses were statistically significantly greater for the majority of comparisons of semaglutide versus dulaglutide within each subgroup category and, excepting glycaemic control within the low-dose comparison in HbA1c subgroups, this was irrespective of subgroup or dose comparison. Gastrointestinal adverse events, the most common with both treatments, were reported by more women than men and, with semaglutide, decreased with increasing BMI. Conclusions: Consistently greater improvements in HbA1c and BW with semaglutide versus dulaglutide, regardless of age, sex, diabetes duration, glycaemic control and BMI, support the efficacy of semaglutide across the continuum of care in a heterogeneous population with T2D. Trial registration number: NCT02648204 .